URINARY STONE COMPOSITION ANALYSIS IN INDONESIAN POPULATION: A SINGLE MAJOR CENTRE ANALYSIS - Widyasmara, Her Bayu; Birowo, Ponco; Rasyid, Nur (Indonesian Journal of Urology, 2018)
Objective: To evaluate the urinary stone composition of Indonesian population. Material & Methods: This is a retrospective study analyzing total 277 urinary stone, obtained from urinary stone patient that underwent treatment in Cipto Mangunkusumo Hospital Jakarta in period 2000-2013. Results: Urinary stone disease is more common in male, with male : female ratio 1.8 : 1, with both in male and female patient, the incidence are highest at 51-60 years old. Calcium containing stone is predominant in this study with calcium oxalate as the most frequent stone with 61% overall, 43.7% in male and 17.3% in female and founded most frequent in 51-60 years old. Uric acid become the second most common stone after calcium containing stone with 9.0% overall, 6.5% in male and 2.5% in female. Infection associated stone such as struvite is 5.8% and Amonium urate 0.7%. In our study, struvite is founded more in male 3.6% than in female 2.2%. Cystine is a rare stone which is only founded 0.7%, in young age at 21-30 years old. Conclusion: Calcium oxalate is the most frequently stone type in our country as it is worldwide. This study revealed  information of stone composition in Indonesian population, that could be beneficial for strategies and management to prevent urinary stone disease and recurrence.